ANALISIS PERHITUNGAN TARIF BIAYA PELABUHAN KAPAL NASIONAL DAN KAPAL ASING DI PELABUHAN TANJUNG PRIOK - Vivian Karim Ladesi; ANINDIYA FITRIANA (Universitas Negeri Jakarta, 2020)
The selection of this Final Project aims to analyze the calculation of the cost tariff for the port of national ships and foreign ships at the Port of Tanjung Priok and the factors that influence the comparison of the port cost rates for national ships and foreign ships to be used as an evaluation material for the port and determine the port rates so that service services to be more efficient and economical. The method used in the preparation of this final project is the literature method, interview study and field observation study. The tariff for port services must have a balance between the amount of the tariff and the level of service received by service users, including safety, security, smoothness and comfort. In encouraging the investment climate and creating efficient and competitive port service tariffs, it is necessary to rearrange the types of structures, categories and mechanisms for determining port service tariffs. One of the factors causing the comparison of port cost rates which causes foreign ship port rates to be higher is the service factor because services at the port are not efficient so that to get customer satisfaction / port service users still charge a higher tariff for each activity. The selection of this Final Project aims to analyze the calculation of the cost tariff for the port of national ships and foreign ships at the Port of Tanjung Priok and the factors that influence the comparison of the port cost rates for national ships and foreign ships to be used as an evaluation material for the port and determine the port rates so that service services to be more efficient and economical. The method used in the preparation of this final project is the literature method, interview study and field observation study. The tariff for port services must have a balance between the amount of the tariff and the level of service received by service users, including safety, security, smoothness and comfort. In encouraging the investment climate and creating efficient and competitive port service tariffs, it is necessary to rearrange the types of structures, categories and mechanisms for determining port service tariffs. One of the factors causing the comparison of port cost rates which causes foreign ship port rates to be higher is the service factor because services at the port are not efficient so that to get customer satisfaction / port service users still charge a higher tariff for each activity.